Melamine, Asam Suanurat dan Melamin-Sianurat: Kaitan dengan Penyakit Saluran Perkencingan Hewan - Yanuartono Yanuartono; Alfarisa Nururrozia; Soedarmanto Indarjulianto; Hary Purnamaningsih; Slamet Rahardjo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
Numerous cases of acute renal failure in dogs and cats from 2004-2007 were associated with the ingestion of dog and cat pet food products and the suspected contaminant was identified as melamine and its derivatives such as cyanuric acid and melamine cyanurate. Melamine is a chemical used primarily for the manufacture of plastics, coatings, commercial filters, adhesives and compounds in the plate-making industry and kitchen appliance.But then these compounds have been abused to increase the content of nitrogen compounds in human food products and animal feed products, respectively. Increasing the content of nitrogen compounds from melamine aims to increase the value of false protein food and feed. Melamine basically has a wide security limit so it is relatively non-toxic if consumed by humans and animals. However, many studies and case reports show that melamine can cause damage to the kidneys especially if present together with cyanuric acid in the body.This paper aims to provide a simple overview and discussion in cases of damage to the urinary tract in dogs and cats that are likely caused by toxicity of melamine and its derivatives are likely to have occurred in Indonesia.